Perancangan Desain User Interface Mobile Apps Pada Sistem Penanggulangan Gawat Darurat Terpadu D.I.Y - dwi nugroho (Jurnal Sistem Informasi Kesehatan Masyarakat, 2022)
Background: Emergency incidents that occur in Indonesia are increasing day by day, both emergency incidents due to traffic accidents and incidents due to disease. The Indonesian government issued PERMENKES number 19 of 2016 concerning the Integrated Emergency Management System, in the creation of the SPGDT it is expected to be able to handle emergency cases in an integrated manner so as to minimize cases of disability and death. The Yogyakarta Special Region Health Service is currently running well in the implementation of SPGDT, but currently, the SPGDT application does not have the Mobile-Apps feature, especially on the Tracking Ambulance menu. With the ambulance tracking menu, people can easily make ambulance calls based on emergency cases that occur and also people don't need to worry if they find an emergency incident but the ambulance doesn't come, with ambulance tracking people can also see the movement of an ambulance that is on "standby" or in the process of “evacuating” an emergency event. Methods: the method in this research is the action research method. This action research method was chosen because the stages of action research start from diagnosis, planning, action and evaluation. Results: the results of this study, at the stage of identifying needs based on user actors. At the planning stage, what data flows are designed, created and the features needed. At the action stage, it produces a user interface design with Figma. At the evaluation stage, the final prototype score was assessed based on the System Usability Scale (SUS) questionnaire with the final score on the driver page prototype getting a final score of 62, while the prototype for paramedics got a final score of 71. And finally, the general public prototype got a final score of 69Conclusions: The process of developing the design, planning and implementation of the mHealth application services requires the collaboration of various sectors, both from the user side from the health side. Feedback from various responses is the key to success to ensure the relevance and sustainability of the mHealth application services. Providing useful and easy-to-use and ensuring continuity of technical support can help smooth the process of using the mHealth application in day healthcare.